Variation in the Abies religiosa (Pinaceae) forest structure, at different management and disturbance conditions - Hernández-Álvarez, Adriana Gisela; Reyes-Ortiz, José Luis; Villanueva-Díaz, José; Sánchez-González, Arturo (Instituto de Ecología, A.C., 2021)
Background and Aims: Abies religiosa forest or sacred fir forest is distributed in isolated patches and its largest continuous areas are located in the Transmexican Volcanic Belt. There are several studies that provide essential information on ecological and floristic aspects of the sacred fir forest in Mexico. However, basic ecological questions still need to be answered, which can be very useful to propose and establish management and conservation strategies for this type of vegetation. For this reason, the objectives of this investigation were: (1) to estimate the variation in the population structure of Abies religiosa and, (2) determine the tree and shrub structure and composition of the sacred fir forest, under different conditions of management and elevation. Methods: The study area included five localities with sacred fir forest in Hidalgo State, with different management and altitude conditions. In total, 25 sampling plots were placed (0.01 ha each), to obtain standard data at the population level (height, density, diameter) and community level (density, basal area and frequency of species). Key results: Three populations of A. religiosa were classified as dynamic due to the predominance of small individuals. The remaining two were normal with a predominance of intermediate-sized specimens. At the community level, 15 species of trees and 15 of shrubs were recorded. The structure of the forest differed in some localities, mainly among the farthest geographically, confirming the role of forest management, and local environmental conditions. Conclusions: Abies religiosa dominated the canopy in all localities. The structural characteristics at both population, and community levels differed between sampling locations, probably due to the forest management and the different local environmental conditions.